PENGARUH MEDIA ALFABET CARD (KARTU HURUF) UNTUK MENINGKATKAN KETERAMPILAN MEMBACA PERMULAAN PADA MATA PELAJARAN BAHASA INDONESIA DI KELAS II SD GMIT MURIABANG - Petrus Mau Tellu Dony (CV. ADIBA AISHA AMIRA, 2025)
The problem formulation in this study is the influence of the Alphabet Card Media to improve beginning reading skills in Indonesian language subjects at Muriabang GMIT Elementary School. This study uses a pre-experimental quantitative research method with a one-group (pretest-posttest) approach. Data collection techniques are validation and tests. The validation results by the subject matter expert were 85% with a feasible category. In addition, in the assessment format aspect which consists of 5 indicators, the assessment score obtained was 23, from the material content aspect which consists of 7 indicators, the assessment score obtained was 27, while the language assessment aspect consists of 4 indicators, the assessment score obtained was 18. All three aspects were categorised as Very Good. Meanwhile, the media was 80% with a feasible category. In addition, in the appearance aspect of the assessment, which consists of 6 indicators, the score obtained was 25, from the presentation aspect, which consists of 8 indicators, the score obtained was 30, while the security assessment aspect used consists of 2 indicators, the score obtained was 9. All three aspects are categorized as ‘worthy’. The use of the Alphabet Card media has led to an improvement in students' reading skills. This is proven by the Paired Sample t-Test with the results obtained, namely Sig. (2-tailed) of 0.000001, which falls into the category of <0.05. The use of Alphabet Card media has a very large influence. This is also seen from the tcount of 6.001> 2.073, which means that the results between the pre-test and post-test classes are very significant.